Crossroads experiences for promoting self-authorship of clinical medical students: A qualitative survey - Mehrnaz Zarei; Shahram Yazdani; Fakhrolsadat Hosseini; John Sandars (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: The capacity of self-authoring one's own beliefs, identity, and relationships is core to many expected outcomes of future health-care professionals. Students' personal and professional development for self-authorship can be promoted by the variety of developmentally effective "crossroads" experiences that they encounter. Identifying the characteristics of the crossroads experiences in clinical rotations can provide a foundation for medical educators to provide an environment that can foster self-authorship. MATERIALS AND METHODS: A cross-sectional qualitative survey was conducted using a researcher developed semi-structured questionnaire which had three open questions and asked medical interns to describe their internship experiences that stimulated their thinking along the self-authorship dimensions of identity, relationships, and ways of knowledge acquisition. Data were analyzed using Braun and Clarkes' thematic analysis method. RESULTS: The survey was completed by 167 medical interns (response rate: 83%). The key features of significant crossroads experiences and their effects were created into six themes: Experiences by being respected and validated; experiences by involvement in patient management; experiences by participation in interactive learning environments; experiences by participation in authentic clinical work environments; experiences by the observation of professional behaviors; experiences through the uniqueness of different specialties. CONCLUSION: Authentic experiences of patient management in the real world of clinical settings with a high interactive environment have the potential to promote interns' self-authorship development. Educators can support learners by respecting and validating their capacities and by role modeling of professional behaviors.